Volumetric evaluation of various obturation techniques in primary teeth using cone beam computed tomography - An in vitro study - N B Nagaveni; Sneha Yadav; P Poornima; K P Bharath; Mebin George Mathew; P G Naveen Kumar (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of this study was to compare and evaluate the efficiency of five different obturation methods in delivering the filling material into the canals of primary teeth using cone beam computerized tomography (CBCT) scan. Method: A total of fifty prepared canals of primary teeth which further divided into five groups with ten canals in each group were obturated with zinc oxide-eugenol cement using five different obturation methods such as endodontic plugger, lentulo spiral (handheld), lentulo spiral mounted on slow speed handpiece, local anesthetic syringe, and tuberculin syringe. Using CBCT scan, the pre- and post-obturation volume and the percentage of obturated volume (POV) were calculated for each group. The results obtained were statistically analyzed using one-way analysis of variance and Tukey's post hoc test. Results: Following CBCT scan, the method obturated with lentulo spiral mounted to handpiece showed the highest POV value followed by the method of lentulo spiral mounted to handpiece, hand plugger, and tuberculin syringe. Local anesthetic syringe gave the least POV (P < 0.05). Conclusion: Lentulo spiral mounted to handpiece showed the best technique of obturation using CBCT evaluation among the five groups evaluated in primary teeth. However, more studies are highly essential to prove it a boon for estimating obturation quality in primary teeth.